Antioxidants and methimazole in the treatment of Graves' disease: Effect on urinary malondialdehyde levels - Guerra, Liliana Noemi (2005)
We have postulated that metabolic oxidation could be the source of signs and symptoms of hyperthyroidism. The present study was designed to evaluate urinary malondialdehyde levels in Graves' disease and compare this oxidative stress biomarker with the clinical evolution of patients suffering this illness. We evaluated the concentration of urinary and serum malondialdehyde (MDA) in 36 patients with Graves' disease. Patients were treated with the antithyroid drug methimazole (MMI; Group A) or antioxidant mixture (200 mg vitamin E, 3 mg β-carotene, 250 mg vitamin C, 1 mg Cu, 7.5 mg Zn, 1.5 mg Mn, and 15 μg Se; Group B). MDA concentrations were higher in hyperthyroid patients compared to euthyroid controls, and a positive correlation was observed between serum and urinary MDA levels. Group A decreased urinary MDA to control values. There was a positive correlation between the clinical score and the heart rate of patients with urinary MDA before and during the treatment with MMI (Group A). Similar results were observed after treatment with the antioxidant mixture. Urinary MDA might be a good parameter in the follow-up of patients during MMI treatment. We proposed that oxidative stress correlates with signs and symptoms of hyperthyroidism.